The Birth of a building : from conception to delivery - Stevens, Ben ([United States] : [Skyline Forum], 2019)
We spend most of our lives in buildings and see new ones being created around us all the time. But the number of people and disciplines involved in a building's creation make it hard to understand the process as a whole. The Birth of a Building is an introduction to those aspects of finance, law, urban planning, architecture, engineering, construction, and real estate development which underlie this fascinating event. Part One focuses on the "birds and the bees," explaining the economic story which motivates people to create new buildings in the first place. Part Two focuses on the longer pregnancy and delivery process, walking you through the specific stages that a building project will pass through. Every chapter begins with a simple analogy from everyday life that helps the total beginner relate to the subject matter. And because it takes an interdisciplinary approach, The Birth of a Building can serve as an introduction to many different fields.
Part One -- Return -- The Cycle -- Capital -- The Pressure to Invest -- Income -- Above the Line -- Weighting for Return -- Waiting for return -- Today's Dollars -- Conclusion to Part 1. -- Part Two -- Forecasting -- Land -- Design -- Approvals -- Entity formation -- Financing -- Construction -- Opening -- Conclusion.
Includes index.
Keywords: REAL PROPERTY -- FINANCE